Diversidade de espécies zooplanctônicas em uma planície de inundação neotropical : influência da predação, das variáveis limnológicas ou da disponibilidade de alimento? - Leal, Clarice Maria (2010)
The structure of zooplankton community in the Upper Paraná River floodplain has examined for two decades, and significant contributions have been made regarding the influence of biotic and abiotic factors on these. Beyond environmental conditions and food availability, the species diversity of a community may also be influenced by predation. Studies concerning trophic ecology of fish, in lakes at this ecosystem, pointed for the occurrence of the zooplankton in the diet of many fish species. The present study assessed the influence of abiotic conditions, food availability and predation on the diversity of zooplankton community, in marginal lakes from this floodplain. We agree that the predation is predominant to other factors on the zooplankton diversity. Sampling was performed every three months from 2000 to 2009, in the pelagic region of six marginal lakes from the floodplain. The limnological variables were preponderant to explain the variations in zooplankton diversity, mainly during the years with larger amplitudes of potamophase. Only in 2008 the species richness estimated via rarefaction presented an inverse relationship with fish biomass. The great contribution of rotifers and testate amoebae for the diversity values seems to support the idea that the predation by small sized.